Clinical Outcomes and Urodynamic Effects of Tailored Transvaginal Mesh Surgery for Pelvic Organ Prolapse. (8th November 2015) - Chang, Ting-Chen; Hsiao, Sheng-Mou; Chen, Chi-Hau; Wu, Wen-Yih; Lin, Ho-Hsiung
Abstract : Objective . To evaluate the clinical outcomes and urodynamic effects of tailored anterior transvaginal mesh surgery (ATVM) and tailored posterior transvaginal mesh surgery (PTVM). Methods . We developed ATVM for the simultaneous correction of cystocele and stress urinary incontinence and PTVM for the simultaneous correction of enterocoele, uterine prolapse, vaginal stump prolapse, and rectocele. Results . A total of 104 women enrolled. The median postsurgical follow-up was 25.5 months. The anatomic cure rate was 98.1% (102/104). Fifty-eight patients underwent urodynamic studies before and after surgeries. The pad weight decreased from 29.3 ± 43.1 to 6.4 ± 20.9 g at 3 months. Among the 20 patients with ATVM, 13 patients had objective stress urinary incontinence (SUI) at baseline while 8 patients came to have no demonstrated SUI (NDSUI), and 2 improved after surgery. Among the 38 patients who underwent ATVM and PTVM, 24 had objective SUI at baseline while 18 came to have NDSUI, and 2 improved after surgery. Mesh extrusion ( n = 4), vaginal hematoma ( n = 3), and voiding difficulty ( n = 2) were noted postoperatively. Quality of life was substantially improved. Conclusions . Our findings document the advantages of these two novel pelvic reconstructive surgeries for pelvic organ prolapse, which had a positive impact on quality of life. ATVM surgery additionally provided an anti-incontinence effect. This clinical trial is registered at ClinicalTrials.gov (NCT02178735 ).